E.T., the Extra-Terrestrial [videorecording (DVD)] - Spielberg, Steven, 1946-; Spielberg, Steven, 1946-; Thomas, Henry, 1971-; Stone, Dee Wallace, 1948-; Coyote, Peter (Universal Pictures Home Entertainment, 2017)
The story of a lost alien, befriended by a young boy who helps him return to his planet.